Implementasi Metode Mind Mapping Dalam Pembelajaran Pendidikan Agama Islam Di SDN Banyubiru Widodaren Ngawi - wiba, wiba wiba (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2018)
If we observe carefully in the process of life, humans always think of various things even if they are the slightest. From the process of thinking, humans try to bring up something new. Something that appears in the mind can be in the form of concepts, ideas, ideas or creativity. Therefore, in the human mind, there is a process of receiving a message or memory, then a processing that will be able to produce various brilliant concepts and ideas. In prosses teaching and learning often occurs the process of receiving messages or memory is hampered because the learning strategy used is not right. One of them on the subject of Islamic Education which is identical to the lecture method. This causes students to be passive and even inhibit creativity and student motivation. One alternative that can be done is to use the Mind Mapping learning method. Alternative learning strategies that can be applied to achieve the competencies that have been set. Based on this research, it was concluded that the implementation of Mind Mapping in the learning of Islamic Education at SDN Banyubiru Widodaren Ngawi was quite good. This strategy is very helpful for students to be active and can increase motivation, creativity and interest in student learning. Keywords: Mind Mapping, motivation, creativity, interest and learning achievement.